STATCOM optimization using ant colony optimization technique / Hairuddin Abdullah - Abdullah, Hairuddin (2008)
In recent practice, the use of flexible AC Transmission System (FACTS) devices has been proposed for enhancement of power grid protection and control in power system by improving the stability, reduction of losses, and reduction of generation cost and improves the laudability of the system. However, prohibitive cost is major stumbling block for utility company to install more than a few FACTS devices on any power grid. Low Environmental Impact technologies such as FACTS Devices and DC links provided solution to rapidly enhancing reliability and up-grading transmission capacity on a long term and cost effective basis. This thesis presents STATCOM optimization using full ACO technique. The study involved the application of ACO technique for the determination of optimal sizing of STATCOM installed on a transmission line for loss minimization in power system IEEE reliability test system was used for validation purposes.